Hubungan Iklim Organisasi Dan Kualitas Kehidupan Kerja Terhadap Komitmen Organisasi: Peran Mediasi Kepuasan Kerja - Siti Nur Azizah; Sri Anggraeni (Majalah Imiah Manajemen & Bisnis, 2022)
The purpose of this study was to determine the effect of organizational climate and quality of work life on organization commitment with job satisfaction as an intervening variable in civil servant employees UPTD Public health center Poncowarno. The sampling method used in this study is nonprobability sampling with purposive sampling technique. The total sampling in this study was 31 respondents. Methods of data collection using questionnaire using a Likert scale of 4 categories. The data analysis used was the validity and reliability instrument test, classical assumption test, hypothesis test and path analysis using SPSS 23.0 for windows.The results of this study indicate that based on the validity and reliability test all variables are declared valid and reliable. Both structural models meet the criteria for classical assumption test with no multicolinearity, heteroscedasticity, and meet the assumption of normalty. Based on the t test, organizational climate has no effect on job satisfaction. Quality of work life has a significant on job satisfaction. Organization climate has a significant on organization commitment. Quality of work life has no effect on organization commitment. Job satisfaction has a significant on organizational commitment.